Resolving the Papua Conflict: A Multidimensional Approach and the Role of Interagency Cooperation - Anas, Muhammad Riza Fathu; Sukendro, Achmed; Malik, Ichsan; Widodo, Pujo; Chandra, Arlina Alfiani (CV. AFDIFAL MAJU BERKAH, 2024)
The conflict in Papua is the longest-running conflict in Indonesia. It began when Indonesia claimed the entire Dutch East Indies territory, including West Papua, on August 17, 1945, leading to prolonged escalation of the conflict. This research aims to analyze conflict resolution in Papua through a multidimensional approach and the role of interagency cooperation to achieve peace in Papua. The methodology used in this research is qualitative method to discover new understandings and provide recommendations for conflict resolution using the concept of interagency cooperation. Findings indicate that the conflict in Papua involves various dimensions, including social, economic, political, cultural, and security aspects. Despite being granted special autonomy, economic disparities and human rights violations continue to persist. Conflict resolution requires coordinated interagency cooperation, involving the government, military, police, NGOs, and international organizations to achieve sustainable peaceful resolution.